Management of Pearl millet smut through cultural practices and fungicides - V. L. MAJUMDAR, R. L. MEENA, A. C. MATHUR1 and (Indian Phytopathology, 2012)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is an important cereal and fodder crop in arid and semi-arid tropics of the world. Smut of Pearl millet caused by Moesziomyces penicillariae (Bref.) Vanky is capable of causing losses upto 30 per cent. Three experiments were conducted during kharif 2004 and 2005 to investigate the effect of different sowing dates, intercropping and popular fungicides against the disease. Early sown crop was found more affected as compared to that of late sown. The maximum smut severity (12.69%) was recorded in earliest sown crop (15th June) followed by (11.56%) in 25th June sown crop. The lowest smut severity (6.70% and 7.94%) was observed in late sown crop. Pearl millet was intercropped with Mungbean, Mothbean, Cowpea and Clusterbean and lowest smut severity (4.5%) was observed with Mungbean followed by intercropping with Mothbean (7.4%) and Cowpea (8.4%). In case of fungicides all the fungitoxicants i.e. Carboxin, Carbandazim, Copper oxychloride, Mancozeb, Hexaconazole and Propiconazole reduced smut significantly as compared to control. In the past Carboxin has been recommended for the control of smut but in the present studies Hexaconazole and Propiconazole have expressed their superiority over Carboxin giving 97.63 and 97.43 per cent disease control respectively.